The Relationship Between Physical Activity Level and Exam Anxiety Level in University Students: A Cross-Sectional Study (International Journal of Scientific Research and Management (IJSRM), 2020)
Introduction: Anxiety, depression and other mental problems are one of the important health problems on university campuses. The anxiety created by the exams in the students negatively affects the students’ attitude and success towards the lessons. The studies carried out, the understanding the relationship between exercise, depression and anxiety, and positive results obtained were satisfying and also increased the value given to this issue. In our study, we examined the relationship between university students’ physical activity level and exam anxiety. Material-Method: This cross-sectional study was conducted with 175 volunteer university students who did and did not do sports. The International Physical Activity Assessment Questionnaire (IPAQ) Long Form was used to measure the level of physical activity and the Exam Anxiety Inventory to determine the level of anxiety. Results: The rate of female patients was significantly higher in the inactive group than the minimally active and active group (p ˂ 0.05). In the inactive group, the test anxiety score was significantly higher (p ˂ 0.05) than the minimally active and active group. Conclusion: As a result, our research revealed that the physical activity levels of university students are quite low, especially in female students, and there is a relationship between the level of physical activity and anxiety.